2018
DOI: 10.1039/c8ja00077h
|View full text |Cite
|
Sign up to set email alerts
|

Multi-energy calibration as a strategy for elemental analysis of fertilizers by microwave-induced plasma optical emission spectrometry

Abstract: Multi-energy calibration was used to determine As, Ba, Cd, Cr, and Pb in fertilizers by MIP OES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Otherwise, when the value was corrected to the mass fraction, the recovery was lower. According to the results shown in Table 2, it can be observed that the best results (highlighted concentrations) were obtained when C Std was at least twice or equal to the analyte concentrations in the sample, as reported by Machado et al 15 The EC, IS, and SA calibration procedures were accomplished in a comparative study. To evaluate these calibrations, we calculated the recoveries of the analytes, that are shown in Table 3.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Otherwise, when the value was corrected to the mass fraction, the recovery was lower. According to the results shown in Table 2, it can be observed that the best results (highlighted concentrations) were obtained when C Std was at least twice or equal to the analyte concentrations in the sample, as reported by Machado et al 15 The EC, IS, and SA calibration procedures were accomplished in a comparative study. To evaluate these calibrations, we calculated the recoveries of the analytes, that are shown in Table 3.…”
Section: Resultsmentioning
confidence: 65%
“…During the calibration process, these lines are merely discarded. [14][15][16] After the analysis of the wavelengths for each analyte, the emission lines were selected, resulting in 18 emission lines for Ca, 9 emission lines for Cu, 12 emission lines for Fe, 11 emission lines for K, 12 emission lines for Mg, 11 emission lines for Na, 14 emission lines for P, 12 emission lines for S, and 14 emission lines for Zn. Each selected emission line represents a point on the calibration curve, as was previously mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…In general, MEC-based methods enable higher trueness compared with EC and IS, and higher sample throughputs compared with SA (as fewer calibration solutions are required per sample). 81,82 An exclusive advantage of the MEC method is the possibility of readily identifying spectral interferences on different emission lines (which manifest as points off the linear region of the MEC plot). In a traditional method, the identication of overlapping peaks would require a pre-analysis study to evaluate potentially interfering elements present in the sample.…”
Section: Calibration Strategiesmentioning
confidence: 99%
“…In the same vein, Tiwari et al ( 2022 ) utilized a panel dataset from 16 Asian economies covering 1990 to 2019 to investigate the equity market-renewable energy nexus. The novel technique of panel quantile regression proposed by Machado et al ( 2018 ) was employed as an estimator. The result shows that developing the equity market encouraged renewable energy projects of 70% quantile.…”
Section: Literature Reviewmentioning
confidence: 99%